2022
DOI: 10.3390/su142316075
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Tourism Potentials of Ethno-Cultural Attractions in Lombok

Abstract: This article is aimed at identifying the potential of various ethno-cultural practices in the Sasak community with a view of developing them as ethno-cultural attractions to sustain tourists to stay longer in Lombok. Various ethno-cultural practices in relation to folklore, festivals, sports, music, food, beverage, and cultural events were identified, and the tourism potentials were also measured. Data were collected by directly observing and video-recoding the ethno-cultural events, interviewing cultural lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Collection of folklore Enige Sasakse Volksvertelsels (Lombok) by Dr. C. Hooykaas, with its review of literary ecocriticism, has never been examined by academics. The majority of academics examine the folklore of the Sasak tribe of Putri Mandalika, such as research conducted by Lestari & Yusra (2022) which says that Sasak tribal folklore including the folklore of Putri Mandalika should be considered as a tourist attraction on Lombok Island from the ethno-cultural side, Wahidah (2019) also examines the folklore of Putri Mandalika from an ethnolinguistic perspective. Cultural values and morality in the folklore of Putri Mandalika have been examined by Ajiani & Hamidah (2020) and Al-Madia & Ichsan (2022), the value of character education in the folklore of Putri Mandalika has been studied by Karhi et al (2021), and the sociological aspects in the folklore of Putri Mandalika have been examined by Basri & Ahmadi (2023).…”
Section: Literature Review Sasak Tribe and Sasak Tribe Folklorementioning
confidence: 99%
“…Collection of folklore Enige Sasakse Volksvertelsels (Lombok) by Dr. C. Hooykaas, with its review of literary ecocriticism, has never been examined by academics. The majority of academics examine the folklore of the Sasak tribe of Putri Mandalika, such as research conducted by Lestari & Yusra (2022) which says that Sasak tribal folklore including the folklore of Putri Mandalika should be considered as a tourist attraction on Lombok Island from the ethno-cultural side, Wahidah (2019) also examines the folklore of Putri Mandalika from an ethnolinguistic perspective. Cultural values and morality in the folklore of Putri Mandalika have been examined by Ajiani & Hamidah (2020) and Al-Madia & Ichsan (2022), the value of character education in the folklore of Putri Mandalika has been studied by Karhi et al (2021), and the sociological aspects in the folklore of Putri Mandalika have been examined by Basri & Ahmadi (2023).…”
Section: Literature Review Sasak Tribe and Sasak Tribe Folklorementioning
confidence: 99%
“…Music can help to enhance the quality of a tourist destination's offering. Music tourism can be viewed through its positive economic and social aspects (Hutabarat 2022;Borges et al 2021;Jenkins and Bristow 2022) such as growing numbers of tourist arrivals, greater income generated, higher employment rates (Getz and Page 2016); new entrepreneurial initiatives (Lestari and Yusra 2022); cultural exchange between residents and visitors, and the creation of a positive destination image (Madani 2022). The negative effects of music festivals are often seen as impacts on the environment with regard to waste management, noise generation, deterioration of residents' quality of life, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Koo et al (2013) reported that tourism language services in Korea are provided real-time using smart technologies, tourism channels, websites, SNS, and mobile applications, and in their view, smart tourism with technologically based smart-tourism language services will be the future direction of world tourism. Lestari and Yusra (2022) has illustrated that tourists visiting Lombok's cultural heritage tourism objects expected the cultural practices on offer to be performed in the native language as a way of presenting culturally authentic attractions. To a great extent, these instances exemplify the linguistic turn in tourism because language, as Heller et al ( 2014) and Jaworski and Thurlow (2010) have suggested, is the only means through which a mode of industrial management in tourism can be implemented where texts and interactions are employed or commoditized for the provision, promotion, and monitoring of tourism sales.…”
Section: Literature Reviewmentioning
confidence: 99%
“…International tourists have once again outnumbered Indonesian-speaking ones. Lestari and Yusra (2022) have shown that, in 2022 and post COVID-19, tourists visiting Lombok are from the following countries: Singapore 22%, Malaysia 18%, Australia 11%, China 11%, Japan 9%, Korea 5%, Taiwan 4%, East Timor 3.3%, USA 3.25%, and UK 3.1%. With domestic tourists only around 4%, international tourists are more than 95%, and with average planned length of stay around 1.2 day, the local government has to establish a TIC at the local international airport that provides free emergency English language service, promoting local tourism destinations as a strategy for what Heller et al (2014) have illustrated as creative marketing of local tourist objects and, at the same time, negotiating with them to spend more time in Lombok or to plan to revisit Lombok in their next tourism plan.…”
Section: Introductionmentioning
confidence: 99%